Activation of MT2 receptor ameliorates dendritic abnormalities in Alzheimer's disease via C/EBPα/miR‐125b pathway. Issue 2 (1st February 2019) - Tang, Hui; Ma, Mei; Wu, Ying; Deng, Man‐Fei; Hu, Fan; Almansoub, Hasan.a.m.m.; Huang, He‐Zhou; Wang, Ding‐Qi; Zhou, Lan‐Ting; Wei, Na; Man, Hengye; Lu, Youming; et al.
Abstract: Impairments of dendritic trees and spines have been found in many neurodegenerative diseases, including Alzheimer's disease (AD), in which the deficits of melatonin signal pathway were reported. Melatonin receptor 2 (MT2) is widely expressed in the hippocampus and mediates the biological functions of melatonin. It is known that melatonin application is protective to dendritic abnormalities in AD. However, whether MT2 is involved in the neuroprotection and the underlying mechanisms are not clear. Here, we first found that MT2 is dramatically reduced in the dendritic compartment upon the insult of oligomer Aβ. MT2 activation prevented the Aβ‐induced disruption of dendritic complexity and spine. Importantly, activation of MT2 decreased cAMP, which in turn inactivated transcriptional factor CCAAT/enhancer‐binding protein α(C/EBPα) to suppress miR‐125b expression and elevate the expression of its target, GluN2A. In addition, miR‐125b mimics fully blocked the protective effects of MT2 activation on dendritic trees and spines. Finally, injection of a lentivirus containing a miR‐125b sponge into the hippocampus of APP/PS1 mice effectively rescued the dendritic abnormalities and learning/memory impairments. Our data demonstrated that the cAMP‐C/EBPα/miR‐125b/GluN2A signaling pathway is important to the neuroprotective effects of MT2 activation in Aβ‐induced dendritic injuries and learning/memory disorders, providing a novel therapeutic target for the treatment of AD synaptopathy.